Sea otter (Lontra felina) in the Andes of southern Peru - Ugarte Núñez, Joaquín Antonio (2021)
The sea otter, sea cat or chungungo (Lontra felina) is considered virtually an exclusive marine species with a preference for rocky littoral habitats along the Paciﬁc coast of Peru and up to Tierra del Fuego in southern Chile and Isla de los Estados in southern Argentina. This scientiﬁc note presents ﬂuvial records of the sea otter. In the Cotahuasi River (Ocoña River basin) there is a record up to the locality of Sipia, 171 km from the coast and at an altitude of 1,994 m above sea level. In the Colca river basin (Majes basin), the farthest record is in the Mamacocha lagoon in the province of Caylloma, 157 km from the sea and at an altitude of 1,702 meters. There are also other direct and indirect records up to the mouth of these basins. The record of this species in two of the largest rivers in southwestern Peru and not in the others (departments of Moquegua and Tacna) is possibly due to the extremely channeled conﬁguration, which may represent a refuge for this endangered species, in addition to having an abundant food supply. It is considered necessary to include conservation actions in the ﬂuvial distribution of the nutra de mar, because activities such as the construction of dams would signiﬁcantly aﬀect its presence in this space and habitat of its distribution, largely unknown.